APPLYING LEARNING OF SCIENTIFIC APPROACH WITH GUIDED DISCOVERY MODEL TO IMPROVE STUDENT LEARNING OUTCOMES FOR STATIC FLUID - MUFID, TAUFAN (Inovasi Pendidikan Fisika, 2017)
The aim of this research are to described the learning implementation, analyzing the student learning outcomes improvement, and describe the response of students after applied learning of scientific approach with guided discovery model. This research’s location in SMA Al-Islam Krian with sample students from class XI MIPA 1, XI MIPA 2, and XI MIPA 3. The methods of collecting data are validation, test, observation, and questionnaire. The analysis from this research use validation, learning activity sheet analysis, n-gain score, and response questionnaire analysis. Based on this research obtained result that : 1) Implementation from learning of scientific approach with guided discovery model get 100%, its mean that all learning steps have done well, 2) Student learning outcomes in knowledge competence are improving with n-gain score in experiment class is 0,534, in class replication 1 is 0,503, and in class replication 2 is 0,494; every class get medium category, average interpretation score in experiment class is 82,28; class replication 1 is 80,92; and class replication 2 is 79,45. 3) Response of students to learning of scientific approach with guided discovery model get 81,79% with very good category. Based on result above can be concluded that learning of scientific approach with guided discovery model can improve student learning outcomes with medium category. Keywords: scientific approach, guided discovery, learning outcomes, static fluid.